MANAJEMEN PENGELOLAAN SMK PERIKANAN DAN KELAUTAN YANG BERBASIS KEBUTUHAN LOKAL, NASIONAL DAN GLOBAL - Anggi Afriansyah; Fikri Muslim; Vera Bararah Barid; Dini Dwi Kusumaningrum (Jurnal Kependudukan Indonesia, 2020)
This paper aims to analyze the management of fisheries and marine vocational secondary schools in Indonesia. This paper will discuss two parts. The first part is the management of fisheries and marine vocational high schools in Indonesia. The second part is crucial problems in managing vocational schools for fisheries and maritime affairs in Indonesia. The data used in this paper is research data in the Special Region of Yogyakarta in 2018 and several data updates carried out during 2020. This research uses qualitative methods through a combination of data collection techniques, namely interviews, focus group discussion (FGD), and observation. Observations were made at SMKN 1 Sanden, SMKN 1 Temon, and Sadeng Harbor, Gunung Kidul. The results showed that local governments role in developing Fisheries and Marine Vocational High Schools is still not optimal and needs to be improved because it can be optimized to its regional potential. The synergy between the central government and local governments in developing and managing a Fisheries and Marine Vocational School is the crucial factor that needs to be considered.